Predicting future stars: Probability and performance corridors for elite swimmers - Born, D.-P.; Stöggl, T.; Lorentzen, J.; Romann, M.; Björklund, G. (Journal of Science and Medicine in Sport, 2024)
Objectives To evaluate the new age groups of the World Junior Championships in swimming from a scientific perspective, establish benchmarks and performance corridors that predict success at peak performance age and compare performance corridors between men and women and short-, middle-, and long-distance freestyle races.